2002
DOI: 10.1007/s005950200098
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Budd-Chiari Syndrome with Percutaneous Transluminal Angioplasty: Report of a Case

Abstract: We report the successful treatment of Budd-Chiari syndrome (BCS) due to an obstruction of the hepatic veins. A 19-year-old man developed bleeding esophageal and gastric varices, and a large amount of ascites was thus caused by portal hypertension. BCS complicated by an obstruction of the major hepatic veins was diagnosed after examinations. We performed percutaneous transluminal angioplasty (PTA). This resulted in a great improvement of BCS, a marked decrease in the pressure of the hepatic veins, and the disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Angioplasty showed excellent long‐term results in six patients. Use of angioplasty has been reported in at least 50 patients with BCS 4,29 , 30 . Most of the cases have not had long‐term follow up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angioplasty showed excellent long‐term results in six patients. Use of angioplasty has been reported in at least 50 patients with BCS 4,29 , 30 . Most of the cases have not had long‐term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Use of angioplasty has been reported in at least 50 patients with BCS. 4,29,30 Most of the cases have not had long-term follow up. However, stenosis almost invariably recurred and required repeated dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…These include transjugular intrahepatic portosystemic shunts (TIPS), balloon dilatation angioplasty, and liver transplantation [10][11][12]. Selection of the treatment option depends on the aetiology of BCS, the location and length of the obstruction and the physical status of the patient [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of PTBA is low and there is a high incidence of restenosis after successful treatment [12]. It has been reported that an absence of anticoagulants after successful PTBA may cause restenosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several percutaneous techniques have been reported for treating BCS, including angioplasty, stenting with endoprostheses, and transjugular intrahepatic portosystemic shunt [8][9][10][11]. In recent years, several percutaneous techniques have been reported for treating BCS, including angioplasty, stenting with endoprostheses, and transjugular intrahepatic portosystemic shunt [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%